Development of an EKA application to help tuberculosis patients improve medication adherence and self efficacy - Fuadiati, Lie Liana; Sukartini, Tintin; Makhfudli, Makhfudli; Dewi, Yulis Setiya; Rosyid, Alfian Nur; Qona’ah, Arina (International Journal of Public Health Science (IJPHS), 2024)
Tuberculosis treatment is carried out daily for a long time, causing boredom with taking medication and reducing medication adherence. It results in drug resistance and more prolonged treatment. In response to the situation, this study developed an android-based application called the education, calendar, and medication alarm (EKA) app to improve medication adherence and self-efficacy of tuberculosis patients. Research and development with four steps: evaluation of health education, medication adherence, and self-efficacy; application development; feasibility test; and application socialization. The sample in this study was 38 respondents. This study also uses morisky medication adherence scale (MMAS-8), self-efficacy, and system usability scale (SUS) questionnaires and evaluation sheets to collect the data. Data analysis was done descriptively. The outcomes of the application feasibility test showed that the EKA application received an acceptable value of 81.5 based on acceptance, B value (81.5) based on value scale, an excellent value (81.5) based on adjective rating, and good score (81.5) based on percentile. Socialization on the use of the application goes well, and the patient gets a good understanding and can use the EKA application easily. It proves that the android-based EKA application tested using the SUS questionnaire can be used as a medium for health education and supports medication adherence and self-efficacy.